2023
DOI: 10.21203/rs.3.rs-2518318/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Red Cell Distribution Width among Sudanese Patients with Hypothyroidism

Abstract: Background: Thyroid dysfunction has a strong linkage with anemia. RDW was traditionally regarded as a part of routine evaluation of anemia Elevated RDW level was significantly associated with subclinical hypothyroidism and hypothyroidism. Objectives: The aim of this is study to assess the Red Cell Distribution Width (RDW-CV and RDW-SD) in patients with hypothyroidism. Methodology: This is a case-control laboratory-based study conducted among 50 patients with hypothyroidism as cases (38.50 ± 10.46 years; 36% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…We observed positive correlation between RDW and serum TSH levels indicating that abnormal thyroid hormone levels may affect red blood cell size and RDW levels. Aktas G et al, 20 Guowei Zhou et al, 21 Alexandra P.Bremner et al, 22 and Khalid Abdelsamea et al reported, 23 these studies support our results indicating that abnormal thyroid hormone levels may affect red blood cell size and RDW levels. It has been observed in several studies 20,21,22,23,24 that this hematological parameter is much higher than others, especially in hypothyroidism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed positive correlation between RDW and serum TSH levels indicating that abnormal thyroid hormone levels may affect red blood cell size and RDW levels. Aktas G et al, 20 Guowei Zhou et al, 21 Alexandra P.Bremner et al, 22 and Khalid Abdelsamea et al reported, 23 these studies support our results indicating that abnormal thyroid hormone levels may affect red blood cell size and RDW levels. It has been observed in several studies 20,21,22,23,24 that this hematological parameter is much higher than others, especially in hypothyroidism.…”
Section: Discussionsupporting
confidence: 89%
“…Aktas G et al, 20 Guowei Zhou et al, 21 Alexandra P.Bremner et al, 22 and Khalid Abdelsamea et al reported, 23 these studies support our results indicating that abnormal thyroid hormone levels may affect red blood cell size and RDW levels. It has been observed in several studies 20,21,22,23,24 that this hematological parameter is much higher than others, especially in hypothyroidism. On the other hand, Montagnana et al represented, 7 positive correlations between MCV and serum TSH level.…”
Section: Discussionsupporting
confidence: 89%